CuBr-лазер в задачах визуализации процессов получения наноматериалов - Тригуб М. В. Максим Викторович; Платонов В. В. Вячеслав Владимирович; Федоров К. В. Кирилл Валерьевич; Евтушенко Г. С. Геннадий Сергеевич; Осипов В. В. Владимир Васильевич (2016, 2016)
Заглавие с экрана